Juju Sundin's birth skills with Sarah Murdoch : proven pain-management techniques for your labour and birth - Sundin, Juju; Murdoch, Sarah (Allen & Unwin, 2007)
Explanations about the physiology of pain and what techniques can help ease it help pregnant women understand what bodies experience during labor and what can be done to actively manage the pain. With a combination of professional advice from a 30-year career in obstetric therapy and recommendations from a program-participant’s personal journey, this guidebook offers proven pain-management tips such as movement, breathing, vocalizing, and using stress balls and keywords. All types of birthing methods are described—including short and long labors, natural or epidural labors, and water births. This much-needed resource aids women to prepare for their biggest fear—the pain of labor—and shows them not only how to get through it, but also illustrates the empowerment of managing such pain.
Keywords: gynekologie a porodnictví; Exercise Movement Techniques; Labor Onset; Pregnant People; přirozený porod; Natural Childbirth; techniky cvičení a pohybu; nástup porodu; těhotné ženy; tělovýchovné lékařství